THE EVOLUTION OF LOCAL GOVERNMENT AND SELF-GOVERNMENT IN RUSSIA - T. Yashchuk (Правоприменение, 2017)
УДК 34The article highlights the main stages in the development of local government and self-gov-ernment in Russia. It shows the specifics of each stage. The formation of the Russian state was accompanied by the synthesis of the princely power and the community self-government. The genesis autocracy was accompanied by a struggle with the self-government institutions. The creation of rural and urban self-government in the second half of the XIX century was accom-panied by a debate on the social and public origin of these institutions.The Soviet state was based on the unity of the Soviet system. It concluded the discrete de-velopment of local self-government in Russia. There is no historical strong tradition of local government in this system.Objective of the article is to identify and characterize the main stages of development of local government and self-government in Russia. Show the discrete nature of the develop-ment of local self-government in Russia.The formation of the Russian state was accompanied by the synthesis of princely power and community self-government. Genesis autocracy was accompanied by a struggle with self-government institutions. The absence of territorial self-government in Russia was offset by the presence of social class municipality for a long time. Caste traditions tradition had a negative impact after the establishment of rural and urban self-government in the second half of the XIX century.During the preparation of the reforms and their implementation were discussions of the rela-tionship between the state and the community began in management. As a result, there is the inclusion of local authorities in the sphere of active state regulation. The desire of the county public to the political activity was suppressed by autocracy. The Provisional Government at-tempt to rely on the local self-government to create new authorities ended in failure.The Soviet state was based on a single management system. Certain powers was delegated at the local level. The local authorities have been transferred some resources to implement it. So the system of local budgets was build. The most successful period of the local govern-ment activity accounts for 1920s. The city and district are considered as the territorial foundation of local government. Scientific field formed that studies the feature of local govern-ment in the Soviet conditions.In the 1930s, there is centralization of government. The development of the city is subject to problems of industrialization and development of the rural areas is subject to problems of collectivization. The state policy does not consider the interests of local communities.The liberalization of the political regime in the late 1950s has led to a revival of the idea of decentralization. But decentralization of government is considered solely as an economic rather than a social and political problem. This understanding persisted until the end of the Soviet period.The lack of stable historical tradition of local government negatively affects the municipal development of the Russian Federation.